The effect of moral distress on emergency nurses' job burnout: the mediating roles of hospital ethical climate and moral resilience - Shirong Wu; Yuqing Sun; Zhipeng Zhong; Huanmei Li; Banghan Ding; Qiuying Deng (Frontiers in Public Health, 2025)
BackgroundReducing nurse job burnout is vital for quality care and turnover reduction, particularly in emergency departments. Given that moral distress is a crucial predictor of job burnout, this study seeks to identify factors that can alter this relationship and its underlying mechanisms. The finding is essential for enhancing job satisfaction among emergency nurses and improving patient safety and healthcare quality.MethodsThis study employed a cross-sectional design and was conducted in May 2024 among nurses in the emergency departments of five tertiary hospitals in Southern China. The survey instruments included the General Demographic Questionnaire, Moral Distress Scale-R (MDS-R), Hospital Ethical Climate Survey (HECS), Rushton Moral Resilience Scale (RMRS), and Maslach Burnout Inventory Human Services Survey (MBI-HSS). Descriptive analysis and Pearson correlation analysis were performed using SPSS 27.0. The structural equation model was constructed with AMOS 28.0 software, and Bootstrap testing was conducted.ResultsThe results showed that moral distress directly affected job burnout (β = 0.265, 95%CI [0.114, 0.391]). Hospital ethical climate and moral resilience both played mediating roles in the relationship between moral distress and job burnout (β = 0.161, 95%CI [0.091, 0.243]) (β = 0.216, 95%CI [0.123, 0.337]). Hospital ethical climate and moral resilience play chain mediating roles between moral distress and job burnout (β = 0.090, 95%CI [0.047, 0.161]).ConclusionThe hospital ethical climate and moral resilience play chain mediating roles between moral distress and job burnout. It is recommended that managers pay comprehensive attention to emergency nurses' moral distress. By improving the hospital ethical climate and enhancing nurses' moral resilience, the level of job burnout can be reduced.